The lure of zebrafish in liver research: regulation of hepatic growth in development and regeneration. (June 2015) - Cox, Andrew G; Goessling, Wolfram
Abstract : The liver is an essential organ that plays a pivotal role in metabolism, digestion and nutrient storage. Major efforts have been made to develop zebrafish ( Danio rerio ) as a model system to study the pathways regulating hepatic growth during liver development and regeneration. Zebrafish offer unique advantages over other vertebrates including in vivo imaging at cellular resolution and the capacity for large-scale chemical and genetic screens. Here, we review the cellular and molecular mechanisms that regulate hepatic growth during liver development in zebrafish. We also highlight emerging evidence that developmental pathways are reactivated following liver injury to facilitate regeneration. Finally, we discuss how zebrafish have transformed drug discovery efforts and enabled the identification of drugs that stimulate hepatic growth and provide hepatoprotection in pre-clinical models of liver injury, with the ultimate goal of identifying novel therapeutic approaches to treat liver disease.